The Effect of Workload, Job Satisfaction, and Work Discipline on Employee Performance of PT. BDMN Rantauprapat - Sultanto, Jenny; Elvina, Elvina; Pristyono, Pristyono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
BDMN Rantauprapat in achieving its business goals, of course, will depend on wrong only on the performance of its employees. The performance of employee banking will influence to quality of service that is given to customers and finally can influence the success and sustainability of the bank’s business. Workload, job satisfaction, and work discipline are several factors that are believed to have an influence on employee performance. This study aims to describe and test how much influence variables influence workload, job satisfaction, and work discipline on the performance of employees at PT. BDMN Rantauprapat Good in a manner Partial nor in a manner simultaneous. The number of respondents is 32 people who work in PT. BDMN Rantauprapat. The research results show that partially or simultaneously, variable workload, job satisfaction, and work discipline positive and significant effect on employee performance at PT. BDMN Rantauprapat.